2003
DOI: 10.1001/archsurg.138.12.1283
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cardiac Sympathectomy by High Thoracic Epidural Anesthesia Improves Regional Left Ventricular Function in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Hypothesis:To evaluate the effects of high thoracic epidural anesthesia (TEA) on global and regional myocardial function and on perioperative coronary risk in patients undergoing coronary artery bypass grafting.Design, Setting, and Patients: Prospective and randomized clinical trial blinded for the primary outcome measure of 73 patients scheduled for coronary artery bypass grafting who had a left ventricular ejection fraction of 50%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 35 publications
2
28
0
5
Order By: Relevance
“…The use of high thoracic epidural anesthesia exerts salutary effects on the coronary circulation as well as myocardial and pulmonary function, attenuates the stress response, and provides prolonged postoperative analgesia (24,25,35). In the United States, however, concerns about the potential for neuraxial bleeding (particularly in the setting of heparinization, platelet inhibitors, and CPBinduced thrombocytopenia), local anesthetic toxicity, and logistical issues related to the timing of epidural catheter insertion and management have resulted in limited use of these techniques (22).…”
Section: Class Imentioning
confidence: 99%
“…The use of high thoracic epidural anesthesia exerts salutary effects on the coronary circulation as well as myocardial and pulmonary function, attenuates the stress response, and provides prolonged postoperative analgesia (24,25,35). In the United States, however, concerns about the potential for neuraxial bleeding (particularly in the setting of heparinization, platelet inhibitors, and CPBinduced thrombocytopenia), local anesthetic toxicity, and logistical issues related to the timing of epidural catheter insertion and management have resulted in limited use of these techniques (22).…”
Section: Class Imentioning
confidence: 99%
“…Two studies reported on mid-term (!12 months) results [16,17], eight on short-term ( 30 days) results [18][19][20][21][22][23][24][25] and seven on both [13,[26][27][28][29][30][31], with a total of 237 mid-term deaths by any cause in 5119 patients and 296 short-term deaths by any cause in 9703 patients. Six of the mid-term studies [17,[26][27][28]30,31] described the completeness of their follow-up that ranged from 84% to 100%.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Two studies [16,20] only showed adjusted associations of troponin with all-cause mortality and crude data could not be obtained. Therefore, these studies could not be used for statistical pooling and were only reported descriptively ( Table 2).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that inhibition of sympathetic excitation in HF blunts myocardial fibrosis [8,9,10,11]. Thoracic epidural anaesthesia inhibits thoracic sympathetic activity and provides cardiac protection during cardiac surgery [12,13]. Low concentrations of local anaesthetics introduced via the high thoracic epidural cavity induce high thoracic sympathetic block (HTSB) without effecting sensory and motor nerves.…”
Section: Introductionmentioning
confidence: 99%